Nghiên cứu thành phần Lipit, axit béo và hoạt tính sinh học các mẫu sinh vật biển ngành da gai (Echinodermata) hải sâm, sao biển, cầu gai - Long, Phạm Quốc; Hương, Lê Mai; Minh, Châu Văn; Hương, Trịnh Thị Thu; Nghị, Đỗ Hữu; Phương, Đoàn Lan; Inh, Cẩm Thị; Truyền, Chu Quang (VNU Journal of Science: Natural Sciences and Technology; Vol 20 No 4, 2004)
The content of lipid and fatty acids composition of four samples of Echinodermata of Marine Vietnam:  sea slug(Holothuria martensii Semper); sea uchin and egg  (Echinothrix calamaris (Pallas)); sea star  (Asterina sp.) were determined. Their bioactive such as antimicrobial activity; antioxydant and cytotoxicity activity were tested invitro and discused also.